A carbon-based powder adsorbent material and a method for preparing the same

CN122916133APending Publication Date: 2026-10-16ZHONGYE-CHANGTIAN INT ENG CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611255811.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,该技术方案以原生煤和/或生物质为原料,未涉及碳基或煤基固体废弃物的利用,也未揭示多种废弃物混合使用可能产生的协同效应

Benefits of technology

[0074]1. This invention uses low-value carbon-based or coal-based solid wastes such as semi-coke powder, carbonization and activation screening particles from activated carbon production, screening particles after flue gas purification by activated carbon method, and fly ash as raw materials. The raw materials are widely available and inexpensive, realizing the synergistic resource utilization of various carbon-based or coal-based solid wastes. The project conforms to the national industrial policy of waste recycling and reuse, and has significant environmental and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916133A_ABST
    Figure CN122916133A_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a carbon-based powder adsorption material, and the method comprises the following steps: S1, mixing coke fines, carbonized and activated screening fine particles in an active carbon production process, screening fine particles after flue gas purification by an active carbon method, and fly ash to obtain a mixture; S2, feeding the mixture into a reactor to perform carbonization and activation reactions, and carbon-based powder adsorption material generated in the reaction process is discharged from the reactor with tail gas flow; and S3, performing gas-solid separation on a mixture of the tail gas and the carbon-based powder adsorption material, and collecting fine powder material, so that a finished product carbon-based powder adsorption material is obtained. The application uses multiple carbon-based or coal-based solid wastes as raw materials, utilizes the synergistic effect among the several raw materials, realizes high-value utilization of the carbon-based or coal-based solid wastes, and simultaneously simplifies a process flow, reduces production cost, and reduces environmental pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an adsorbent material and its preparation method, specifically to a carbon-based powder adsorbent material and its preparation method, belonging to the field of adsorbent material preparation technology. Background Technology

[0002] Powdered adsorbent materials are widely used in environmental remediation, industrial wastewater treatment, and exhaust gas purification. Powdered activated carbon, due to its large specific surface area, high adsorption capacity, and stable physicochemical properties, is one of the most commonly used adsorbent materials. Existing powdered activated carbon is typically made from high-quality wood chips, coconut shells, or coal as raw materials, processed through carbonization, activation, and grinding.

[0003] However, traditional raw material resources such as high-quality sawdust, coconut shells, and coal are becoming increasingly scarce. Carbon-based or coal-based solid wastes, such as semi-coke dust after screening in semi-coke plants, carbonization and activation screening particles during activated carbon production, screening particles after flue gas purification using activated carbon methods, and fly ash, are currently usually disposed of in low-value ways such as incineration or landfill, resulting in extremely low resource utilization value.

[0004] Traditional powdered activated carbon preparation processes involve carbonizing and activating raw coal or biomass before grinding. Different particle sizes and adsorption properties are obtained by controlling the activation depth and grinding particle size. To improve the versatility of raw materials and the adsorption performance of powdered activated carbon, many researchers have conducted a series of studies on raw material selection and activation processes. For example, Chinese patent CN106517188A discloses a method for preparing coal-based activated carbon for environmental remediation, involving a solid-liquid-solid multiphase reaction and including multiple wet processes such as organic solvent stirring, acid washing, and water washing. This process is lengthy, complex to control, and prone to leading to unstable product quality.

[0005] Another Chinese patent, CN119038545A, discloses a coal-based powdered activated carbon and its preparation method. This method involves mixing anthracite, lignite, and weakly caking coal, followed by grinding and heat treatment, and then chemically activating the carbon by doping with phosphoric acid or zinc chloride to optimize the pore structure. This method carries the risk of chemical activation corroding equipment and polluting the environment. The manufacturing process is complex, and it is difficult to consistently control product quality.

[0006] Existing technologies also include integrated carbonization and activation processes within the same reactor. For example, Chinese patent CN112029518A discloses a system that integrates carbonization and activation using a fluidized bed reactor, dividing the furnace into an upper activation zone and a lower carbonization zone. However, this technology uses raw coal and / or biomass as raw materials, does not address the utilization of carbon-based or coal-based solid waste, and does not reveal the potential synergistic effects of mixing multiple wastes.

[0007] In summary, existing technologies are limited in raw material selection (mainly relying on raw coal, biomass, or single waste materials), have long production processes and complex process control, and make it difficult to maintain stable product quality. Therefore, developing a carbon-based powder adsorbent material preparation technology with a wide range of raw material sources, a short process flow, less pollution during production, and stable product quality is of great significance. Summary of the Invention

[0008] To address the shortcomings of the existing technologies, this invention provides a method for preparing carbon-based powder adsorbent materials. This method uses various carbon-based or coal-based solid wastes, such as semi-coke fragments, carbonized and activated sieved particles from the activated carbon production process, sieved particles after flue gas purification by activated carbon, and fly ash, as raw materials. By utilizing the synergistic effect between these raw materials, the method achieves high-value utilization of carbon-based or coal-based solid wastes, while simplifying the process, reducing production costs, and minimizing environmental pollution.

[0009] The present invention also provides a carbon-based powder adsorbent material prepared by the above method.

[0010] According to a first embodiment of the present invention, a method for preparing a carbon-based powder adsorbent material is provided.

[0011] A method for preparing a carbon-based powder adsorbent material, the method comprising the following steps:

[0012] S1. Mix semi-coke powder, carbonization and activation sieved granules from the activated carbon production process, sieved granules after flue gas purification by activated carbon method, and fly ash to obtain a mixture.

[0013] S2. The mixture is fed into the reactor for carbonization and activation reaction. The carbon-based powder adsorbent material generated during the reaction is discharged from the reactor with the tail gas flow.

[0014] S3. Perform gas-solid separation on the mixture of exhaust gas and the carbon-based powder adsorbent material, and collect the fine powder to obtain the finished carbon-based powder adsorbent material.

[0015] In this invention, by weight, the mixture in step S1 includes: 50-70 parts of semi-coke powder, 15-30 parts of carbonization and activation screening particles from the activated carbon production process, 10-20 parts of screening particles after flue gas purification by activated carbon method, and 1-5 parts of fly ash.

[0016] In this invention, the reactor mentioned in step S2 is a fluidized bed carbon activation integrated furnace. The furnace chamber of the fluidized bed carbon activation integrated furnace is divided into a lower carbonization zone and an upper activation zone.

[0017] Preferably, the activation zone is activated in an oxygen-containing and steam-containing atmosphere. Preferably, the oxygen generated by air separation is divided into two paths: one path is introduced into the activation zone of the fluidized bed carbon activation furnace to participate in the activation reaction, and the other path is introduced into the bottom of the fluidized bed carbon activation furnace for combustion support.

[0018] In this invention, the oxygen volume percentage of the oxygen-containing and steam-containing atmosphere is 6% to 10%, and the water vapor volume percentage is 30% to 70%.

[0019] In this invention, before mixing the raw materials in step S1, they are crushed and screened to obtain granules with a particle size ≤ 5 mm, preferably granules with a particle size ≤ 4 mm.

[0020] In this invention, a step of preheating the reactor is included before step S2. Preferably, the reactor is preheated to 300~650°C, more preferably 400~600°C.

[0021] In this invention, the carbonization reaction temperature in step S2 is controlled at 600~900℃, preferably 620~850℃, and more preferably 650~800℃.

[0022] In this invention, the activation reaction temperature in step S2 is controlled at 900~1000℃, preferably 900~950℃.

[0023] In this invention, the gas-solid separation in step S3 includes: sequentially subjecting the mixture of exhaust gas and carbon-based powder adsorbent material to primary cyclone separation, secondary cyclone separation, and dust removal. Preferably, the larger carbon-based powder adsorbent material particles separated by the primary cyclone separation and / or secondary cyclone separation are returned to the reactor to continue participating in the activation reaction.

[0024] Preferably, the proportion of particles with a particle size ≤44μm (i.e., 325-mesh sieve undersize) in the finished carbon-based powder adsorbent material is ≥90%, preferably ≥92%. Herein, "325-mesh sieve undersize" refers to fine particles with a particle size not greater than 44μm that can pass through a 325-mesh standard sieve.

[0025] Preferably, a waste heat recovery step is included between the primary and secondary cyclone separations. After the mixture of exhaust gas and carbon-based powder adsorbent material undergoes primary cyclone separation, the carbon-activated exhaust gas containing finer particles of carbon-based powder adsorbent material undergoes waste heat recovery, followed by secondary cyclone separation and dust removal. The collected fine powder is the finished carbon-based powder adsorbent material. Preferably, a portion of the steam generated in the waste heat recovery step is returned to the reactor as an activator to participate in the activation reaction.

[0026] According to a second embodiment of the present invention, a carbon-based powder adsorbent material is provided.

[0027] A carbon-based powder adsorbent material, which is prepared according to the method described in the first embodiment.

[0028] To address the shortcomings of existing technologies, this invention proposes a method for preparing carbon-based powder adsorbent materials using various carbon-based or coal-based solid wastes as raw materials, and the resulting carbon-based powder adsorbent materials. Through the synergistic effect between various specific carbon-based or coal-based wastes, the high-value utilization of carbon-based or coal-based solid wastes is achieved.

[0029] In this invention, a mixture of four carbon-based or coal-based raw materials—including semi-coke powder, carbonized and activated sieved particles from the activated carbon production process, sieved particles from flue gas purification using activated carbon, and fly ash—is fed into a reactor for carbonization and activation reactions. The resulting carbon-based powder adsorbent material undergoes gas-solid separation along with the carbon activation tail gas, and the desired fine powder is collected to obtain the finished carbon-based powder adsorbent material. This invention provides a carbon-based powder adsorbent material preparation technology with a wide range of raw material selection, simple process flow and control, rich and stable product pore structure, and ease of industrial application.

[0030] It should be noted that, in this invention, the meanings of each raw material are as follows:

[0031] Semi-coke dust: Fine particles and powder with a particle size ≤6mm generated during the processing, transportation, and storage of semi-coke, a solid product obtained from the medium- and low-temperature dry distillation of low-rank coal. Semi-coke dust has a high carbon content and low ash and volatile matter content. It is characterized by high fixed carbon and well-developed pores, and belongs to carbon-based solid waste.

[0032] Carbonization and activation screening of broken particles in activated carbon production: Small particles and dust that do not meet particle size requirements are separated during the screening process of activated carbon after carbonization, before activation, or after activation. This raw material has a high carbon content and relatively low ash content, and already has a certain porous structure, belonging to carbon-based solid waste.

[0033] Screened particles after flue gas purification using activated carbon: Activated carbon adsorbs and purifies SO2 and NO in the flue gas during the purification process. x Pollutants such as activated carbon and dust are sent to the desorption tower for thermal regeneration treatment, and then screened by an air screen or vibrating screen to obtain small granular activated carbon and dust. This raw material has undergone regeneration treatment and has formed a relatively rich porous structure during the flue gas purification and desorption process, possessing a certain adsorption capacity, and belongs to carbon-based solid waste.

[0034] Fly ash: Fine ash and bottom ash collected from flue gas in coal-fired power plant boilers by a dust collector. It contains unburned carbon particles and components such as SiO2, Al2O3, Fe2O3, and CaO, and is classified as coal-based solid waste. In this invention, fly ash with a loss on ignition ≤10% is preferred.

[0035] Specifically, the preparation method of the carbon-based powder adsorbent material of the present invention mainly includes the following steps:

[0036] Step S1: Preparation and mixing of raw materials

[0037] The four raw materials are crushed and screened separately: semi-coke powder, carbonization and activation screening granules from the activated carbon production process, screening granules after flue gas purification by activated carbon method, and fly ash. After obtaining granular materials, they are stored separately, then weighed and mixed according to a set ratio to obtain a mixture.

[0038] Before mixing the raw materials, it is preferable to crush and screen them first to control the particle size to within 5 mm (preferably within 4 mm). On the one hand, this can avoid poor fluidization of large particles in the subsequent fluidized bed carbon activation furnace, ensure the fluidization stability in the fluidized bed, and make the carbonization and activation reactions proceed uniformly. On the other hand, it can also shorten the reaction time of carbonization and activation, improve reaction efficiency, and reduce energy consumption. In addition, it can also make the pore structure of the final carbon-based powder adsorbent material more uniform and the adsorption performance more stable.

[0039] In this invention, the preferred proportions of the four raw materials, by weight, are: 50-70 parts of semi-coke powder, 15-30 parts of carbonization and activation sieved particles from the activated carbon production process, 10-20 parts of sieved particles from flue gas purification using activated carbon, and 1-5 parts of fly ash. Within this proportion range, the four raw materials work together to form a synergistic system with complementary functions, producing a significant synergistic effect.

[0040] 1. Semi-coke powder has a high fixed carbon content and well-developed pores, which can provide a sufficient carbon skeleton for the finished product and ensure the overall adsorption capacity of the material.

[0041] 2. The sieved particles produced during the activated carbon production process already have a preliminary pore structure. When mixed and activated, they can reduce the energy consumption for pore expansion in the initial stage of the reaction and accelerate the activation reaction rate.

[0042] 3. The sieved particles after flue gas purification by activated carbon, having undergone thermal regeneration, serve as a "pre-activated synergistic component" in this system. Its abundant existing pore structure...

[0043] (1) Direct integration into the finished product network: These mature channels will not collapse during subsequent activation, but will be directly transformed into the source of mesopores and macropores of the finished carbon, forming a gradient pore size distribution with the newly generated micropores of semi-coke powder after activation.

[0044] (2) Exercising residual adsorption activity and selectivity: It still has adsorption capacity and has active sites of functional groups such as oxygen or nitrogen on its surface, which can improve the surface chemical properties of the finished material and enhance the adsorption capacity and selectivity for specific adsorbates.

[0045] 4. Fly ash plays a dual role in the system: on the one hand, its components such as Fe2O3 and CaO play a catalytic gasification role in the activation process, promoting micropore development and reducing the activation temperature; on the other hand, its low loss on ignition (≤10%) characteristic ensures that the inert components in the ash will not excessively consume the fixed carbon in the system, thus reducing raw material costs while maintaining the yield of finished products.

[0046] This invention, through the synergy of the above four elements, forms a linkage mechanism in which "semi-coke constructs the main framework, production waste induces initial pore formation, recycled flue gas waste contributes mature channels and optimizes pore size gradient, and fly ash provides catalytic support." This mechanism utilizes the inherent mesopores of recycled flue gas waste to compensate for the inherent defect of high mass transfer resistance in semi-coke-based microporous materials, enabling the finished product to achieve both high micropore adsorption capacity and rapid adsorption kinetics, thus realizing the high-value transformation of solid waste resources.

[0047] Step S2, Integrated Carbonization and Activation Reaction

[0048] First, the fluidized bed carbon activation integrated furnace is preheated to the preset temperature. Then, the mixed raw materials are added to the reactor through the feed inlet in the lower part of the furnace. After entering the furnace, larger particles settle to the carbonization zone in the lower section of the furnace due to gravity, completing the carbonization reaction under a non-oxidizing atmosphere, removing most of the volatiles from the raw materials and forming an initial carbon skeleton. Smaller particles rapidly complete carbonization during their ascent and then enter the activation zone in the upper section of the furnace. The material entering the activation zone completes the activation reaction under oxygen-containing and steam-containing atmosphere and high-temperature conditions, developing a rich porous structure and ultimately forming a carbon-based powder adsorbent material, which is discharged from the top of the reactor with the exhaust gas flow.

[0049] This invention employs a fluidized bed carbon activation integrated furnace, completing the carbonization and activation steps within a single reactor in separate zones. This eliminates the need for additional transfer equipment and processes, significantly shortening the process flow and reducing equipment investment and energy consumption. The activation reaction, conducted in an oxygen- and steam-containing atmosphere, accelerates the carbon oxidation and pore-forming rate, shortens activation time, and improves production efficiency. The oxygen obtained from air separation is divided into two paths: one path is introduced into the activation zone to participate in the activation reaction, ensuring the oxygen-containing environment meets the activation requirements; the other path is introduced into the furnace bottom for combustion support, providing combustion assistance for some incompletely reacted combustibles within the furnace, maintaining the reaction temperature within the reactor, and reducing additional fuel consumption. The steam generated from waste heat recovery is reused as an activating agent, further improving energy utilization and reducing material and energy consumption in the production process.

[0050] In this invention, before the mixture enters the reactor for carbonization and activation, it is preferable to preheat the reactor to 300~650℃ (preferably 400~600℃) to avoid a sudden drop in furnace temperature after the raw materials are added, to ensure that the carbonization and activation reactions can proceed quickly and stably, to reduce process control fluctuations, and to ensure uniform and stable product performance.

[0051] The carbonization zone controls the reaction temperature at 600-900℃ (preferably 620-850℃, more preferably 650-800℃), and the carbonization time can be adjusted according to actual needs, for example, it can generally be set to 20-50 minutes. The carbonization process mainly removes volatiles from the raw materials and forms a preliminary porous structure. The activation zone controls the reaction temperature at 900-1000℃ (preferably 900-950℃), and similarly, the activation time can generally be set to 20-50 minutes. Water vapor and oxygen are introduced as activators. Through the oxidation etching and activation etching of carbon, a rich and well-developed porous structure is developed on the carbon skeleton. Part of the introduced oxygen enters the activation zone to participate in the activation reaction, and the other part is introduced into the furnace bottom to assist combustion, providing the heat required for the carbonization and activation reactions and maintaining a stable reaction temperature in the reactor. The activator can be flexibly selected from air + water vapor or oxygen-enriched air + water vapor as needed.

[0052] Materials of different particle sizes behave differently in the furnace: larger particles complete carbonization in the lower section of the furnace and then gradually enter the activation zone, while smaller particles complete carbonization quickly during the upward process and then enter the activation zone with the airflow. Carbonization and activation are carried out in a coupled manner in the same furnace.

[0053] Step S3: Gas-solid separation and finished product collection

[0054] The mixture of carbon-activated tail gas and carbon-based powder adsorbent discharged from the reactor first undergoes a primary cyclone separator to separate larger particles of the carbon-based powder adsorbent. These larger particles are returned to the reactor as feedstock to continue participating in the activation reaction. The carbon-activated tail gas containing finer particles obtained after the primary separation undergoes waste heat recovery. The recovered heat is used to produce by-product steam, part of which is reused as an activator, while the remaining steam can be supplied to other processes. The carbon-activated tail gas after waste heat recovery then undergoes a secondary cyclone separator to separate the larger particles (i.e.,...) Figure 2 The coarse powder in the process is returned to the reactor to continue participating in the activation reaction; the carbon activation tail gas containing finer particles after secondary separation is finally treated by dust removal (e.g., bag filter), and the collected fine powder is the finished carbon-based powder adsorbent material. The separated and purified carbon activation tail gas can be further utilized as a resource (e.g., used as fuel or recovered as heat energy), realizing the cascade recovery of waste heat and chemical energy of the tail gas.

[0055] This invention employs a multi-stage separation process involving primary cyclone separation, waste heat recovery, secondary cyclone separation, and dust removal, combined with secondary activation of returned materials. This process ensures that over 90% of the collected carbon-based powder adsorbent material products have a particle size ≤44μm (i.e., material under a 325-mesh sieve). This guarantees that the particle size of the product meets the requirements, improves the utilization rate of raw materials, and ensures stable product quality.

[0056] The technological principles of this invention include the following points:

[0057] 1. In the lower section of the fluidized bed carbonization and activation integrated furnace, moisture and volatile matter are removed from the material. The removed volatile matter is mixed with the introduced oxygen or air and then burned, continuously supplying heat to the furnace. After the volatile matter is removed, the material undergoes burn-off and forms a preliminary porous structure, reducing its weight. It is then carried by the airflow to the activation zone in the upper section of the furnace, where it undergoes alternating activation reactions with the introduced air, steam, and flue gas.

[0058] 2. During the above reaction process, the carbon matrix is ​​gradually consumed and burned off, and the original defect sites are preferentially etched to form pores, which then develop into pores; the gas generated in the reaction diffuses at the same time, further widening the pore channels, thereby increasing the specific surface area and pore volume of the carbon-based powder adsorbent material and improving its adsorption performance.

[0059] 3. The circulating fluidized bed carbon activation integrated furnace enhances particle circulation within the furnace through a reasonable furnace structure design, resulting in uniform bed temperature distribution. It employs multi-stage cyclone separation and return processes to achieve external bed circulation. The separated solid particles are returned to the furnace to continue participating in the activation reaction, thereby improving the activation yield of carbon-based or coal-based raw materials and enhancing the utilization rate of carbon-based or coal-based solid waste. The use of high-temperature air preheating and steam waste heat recovery processes can improve the quality of carbon activation tail gas and the efficiency of waste heat recovery.

[0060] This invention mixes the above four raw materials and simultaneously performs carbonization and activation reactions in the same reactor, obtaining a carbon-based powder adsorbent material with rich pore structure and excellent adsorption performance through the following multiple synergistic effects:

[0061] (1) Synergistic mechanism of catalytic gasification

[0062] Fly ash contains alkaline metal oxides such as Fe2O3 and CaO. These natural components can catalyze the gasification reaction of carbon with water vapor and CO2 during high-temperature activation, reducing the activation energy and increasing the gasification rate. When fly ash is mixed with other carbon-based wastes, these natural metal oxides are uniformly distributed throughout the reaction system as "self-generated catalysts," continuously promoting the gasification and pore-forming reaction of the carbon matrix. Furthermore, this invention preferably uses fly ash with a loss on ignition ≤10%, ensuring extremely low unburned carbon content. This prevents residual carbon in the ash from excessively consuming the main carbon skeleton during activation, ensuring that the catalytic effect precisely serves the gasification and pore-forming of semi-coke and activated carbon waste, rather than triggering uncontrollable additional combustion.

[0063] (2) Multi-level pore complementary and synergistic mechanism

[0064] The pore structures of the four raw materials are at different developmental stages, forming a "gradient pore-forming" network during simultaneous activation:

[0065] Semi-coke fragments, released during the dry distillation process, possess well-developed macroporous and mesoporous transport channels, which can serve as a rapid diffusion path for activating gases to enter the interior of the particles.

[0066] The carbonized and activated sieved particles in the activated carbon production process already possess a preliminary porous structure, which can serve as a "nucleation substrate" in the early stages of activation.

[0067] After the activated carbon method purifies the flue gas, the sieved particles are purified by flue gas and thermal regeneration, forming a stable and abundant microporous-mesoporous network. These mature channels will not collapse during subsequent activation, but will be directly integrated into the finished product, becoming the main source of mesopores and macropores in the product.

[0068] While the metal oxides in fly ash are catalytically gasified, their inert oxides (SiO2, Al2O3) fine powders act as a rigid skeleton support in the formed green body, preventing excessive particle shrinkage during high-temperature activation.

[0069] This mechanism allows the newly generated micropores from the activation of semi-coke, the inherent mesopores of regenerated charcoal, and the macropores left by the dry distillation of semi-coke to be nested together, ultimately forming a multi-level pore structure with a gradient distribution of "micropore-mesopore-macropore", which not only ensures high adsorption capacity but also significantly reduces mass transfer resistance.

[0070] (3) Reaction thermal field-assisted stabilization mechanism

[0071] The volatile matter content and release temperature windows of the four raw materials differ to some extent. During the simultaneous heating and carbonization activation process, the staggered release peaks of volatile matter from each raw material can, to some extent, neutralize localized overheating or undercooling areas within the reactor, thus playing a supporting stabilizing role in the thermal field uniformity of the carbonization-activation reaction environment. Simultaneously, the high fixed carbon content of the semi-coke fragments provides a stable carbon source supply for the entire carbonization reaction system, ensuring the integrity of the final material's carbon skeleton.

[0072] The four synergistic mechanisms described above are coupled together, enabling the method of this invention to prepare carbon-based powder adsorbent materials with excellent adsorption performance using various low-value carbon-based or coal-based solid wastes as raw materials. The combination of these four raw materials not only solves the problem of unstable performance of single waste components but also achieves synergistic high-value utilization of multiple solid wastes, reducing dependence on high-quality primary raw materials.

[0073] Compared with the prior art, the present invention has the following beneficial technical effects:

[0074] 1. This invention uses low-value carbon-based or coal-based solid wastes such as semi-coke powder, carbonization and activation screening particles from activated carbon production, screening particles after flue gas purification by activated carbon method, and fly ash as raw materials. The raw materials are widely available and inexpensive, realizing the synergistic resource utilization of various carbon-based or coal-based solid wastes. The project conforms to the national industrial policy of waste recycling and reuse, and has significant environmental and economic benefits.

[0075] 2. Through multiple coupling synergistic effects, the four raw materials in this invention can be used to prepare carbon-based powder adsorbent materials with well-developed pore structure and excellent adsorption performance. The product quality is stable and the applicability is wide.

[0076] 3. This invention completes the two key steps of carbonization and activation in the same reactor, eliminating the need for a complex process of separate carbonization, activation, and grinding. This results in high production efficiency and facilitates continuous large-scale production.

[0077] 4. This invention, through multi-stage gas-solid separation combined with a secondary activation process using recycled materials, not only ensures that the particle size of the finished carbon-based powder adsorbent material meets the requirements, but also improves the utilization rate of raw materials and further reduces production costs.

[0078] 5. The process of this invention does not involve chemical activators and generates no wastewater; the exhaust gas can be recycled after waste heat recovery. Attached Figure Description

[0079] Figure 1 This is a flowchart of a method for preparing a carbon-based powder adsorbent material according to the present invention;

[0080] Figure 2 This is a flowchart illustrating the preparation process of the carbon-based powder adsorbent material in Example 1 of the present invention. Detailed Implementation

[0081] The technical solution of the present invention will be illustrated below with examples. The scope of protection sought by the present invention includes, but is not limited to, the following embodiments.

[0082] According to a first embodiment of the present invention, a method for preparing a carbon-based powder adsorbent material is provided.

[0083] A method for preparing a carbon-based powder adsorbent material, the method comprising the following steps:

[0084] S1. Mix semi-coke powder, carbonization and activation sieved granules from the activated carbon production process, sieved granules after flue gas purification by activated carbon method, and fly ash to obtain a mixture.

[0085] S2. The mixture is fed into the reactor for carbonization and activation reaction. The carbon-based powder adsorbent material generated during the reaction is discharged from the reactor with the tail gas flow.

[0086] S3. Perform gas-solid separation on the mixture of exhaust gas and the carbon-based powder adsorbent material, and collect the fine powder to obtain the finished carbon-based powder adsorbent material.

[0087] In this invention, by weight, the mixture in step S1 includes: 50-70 parts of semi-coke powder, 15-30 parts of carbonization and activation screening particles from the activated carbon production process, 10-20 parts of screening particles after flue gas purification by activated carbon method, and 1-5 parts of fly ash.

[0088] In this invention, the reactor mentioned in step S2 is a fluidized bed carbon activation integrated furnace. The furnace chamber of the fluidized bed carbon activation integrated furnace is divided into a lower carbonization zone and an upper activation zone.

[0089] Preferably, the activation zone is activated in an oxygen-containing and steam-containing atmosphere. Preferably, the oxygen generated by air separation is divided into two paths: one path is introduced into the activation zone of the fluidized bed carbon activation furnace to participate in the activation reaction, and the other path is introduced into the bottom of the fluidized bed carbon activation furnace for combustion support.

[0090] In this invention, before mixing the raw materials in step S1, they are crushed and screened to obtain granules with a particle size ≤ 5 mm, preferably granules with a particle size ≤ 4 mm.

[0091] In this invention, a step of preheating the reactor is included before step S2. Preferably, the reactor is preheated to 300~650°C, more preferably 400~600°C.

[0092] In this invention, the carbonization reaction temperature in step S2 is controlled at 600~900℃, preferably 620~850℃, and more preferably 650~800℃.

[0093] In this invention, the activation reaction temperature in step S2 is controlled at 900~1000℃, preferably 900~950℃.

[0094] In this invention, the gas-solid separation in step S3 includes: sequentially subjecting the mixture of exhaust gas and carbon-based powder adsorbent material to primary cyclone separation, secondary cyclone separation, and dust removal. Preferably, the larger carbon-based powder adsorbent material particles separated by the primary cyclone separation and / or secondary cyclone separation are returned to the reactor to continue participating in the activation reaction.

[0095] Preferably, the proportion of particles with a particle size ≤44μm in the finished carbon-based powder adsorbent material is ≥90%, preferably ≥92%.

[0096] Preferably, a waste heat recovery step is included between the primary and secondary cyclone separations. After the mixture of exhaust gas and carbon-based powder adsorbent material undergoes primary cyclone separation, the carbon-activated exhaust gas containing finer particles of carbon-based powder adsorbent material undergoes waste heat recovery, followed by secondary cyclone separation and dust removal. The collected fine powder is the finished carbon-based powder adsorbent material. Preferably, a portion of the steam generated in the waste heat recovery step is returned to the reactor as an activator to participate in the activation reaction.

[0097] According to a second embodiment of the present invention, a carbon-based powder adsorbent material is provided.

[0098] A carbon-based powder adsorbent material, which is prepared according to the method described in the first embodiment.

[0099] The present invention will be further described below with reference to specific embodiments:

[0100] I. Raw Material Sources and Pretreatment

[0101] The sources of raw materials used in the following specific embodiments and comparative examples are as follows:

[0102] Semi-coke dust: Taken from a certain semi-coke enterprise, it has undergone drying treatment before leaving the factory, with a particle size ≤6mm, fixed carbon content of about 84%, volatile matter of about 9%, and ash content of about 6%.

[0103] Carbonization and activation screening of crushed particles in the activated carbon production process: The undersize material collected from the activation screening process of an activated carbon production enterprise has a particle size of ≤5mm, a fixed carbon content of about 83%, and an ash content of about 13%.

[0104] Screened particles after flue gas purification by activated carbon method: The activated carbon after adsorption saturation and analysis was obtained by screening by a vibrating screen. The particle size is ≤2mm, the fixed carbon content is about 70%, and the ash content is about 15%.

[0105] Fly ash: taken from a pulverized coal furnace in a thermal power plant, with a loss on ignition of about 8%, SiO2+Al2O3 content of about 82%, Fe2O3 content of about 5%, and CaO content of about 3%.

[0106] The above raw materials are crushed and screened to obtain granules with a particle size ≤5mm for later use.

[0107] II. Preparation System for Implementing the Invention

[0108] like Figure 2 As shown, the preparation system for implementing the method of the present invention includes: a fluidized bed carbon activation integrated furnace, a primary cyclone separator, a return feeder, a waste heat recovery system, a secondary cyclone separator, a bag filter, a cooler, and a slag cooler.

[0109] The fluidized bed carbon activation integrated furnace has a furnace chamber divided into a lower carbonization zone and an upper activation zone. A feed inlet is located in the lower middle section, an oxygen inlet at the bottom, and an outlet at the top. A slag cooler is also connected to the bottom for cooling a very small amount of bottom slag. The top outlet of the fluidized bed carbon activation integrated furnace is connected to the inlet of the primary cyclone separator; the bottom outlet of the primary cyclone separator is connected to the return port of the upper activation zone of the fluidized bed carbon activation integrated furnace via a return feeder; the top outlet of the primary cyclone separator is connected to the inlet of the waste heat recovery system; the outlet of the waste heat recovery system is connected to the inlet of the secondary cyclone separator; the upper outlet of the secondary cyclone separator is connected to the inlet of the bag filter; the bottom outlet of the secondary cyclone separator is connected to the return port of the upper activation zone of the fluidized bed carbon activation integrated furnace via a return feeder; and the outlet of the bag filter is connected to the inlet of the cooler.

[0110] The waste heat recovery system employs a partitioned heat exchanger, including a steam generator and a water heater, to recover waste heat from the carbon activation tail gas, producing low-pressure saturated steam as a byproduct. The carbon activation tail gas containing powder from the primary cyclone separator enters the waste heat recovery system for heat exchange, producing low-pressure saturated steam as a byproduct. External industrial soft water or demineralized water, after deoxygenation by a deaerator, is pumped into the waste heat recovery system by a boiler water pump. Simultaneously, cold air is introduced into the waste heat recovery system for heat exchange. A portion of the low-pressure saturated steam discharged from the waste heat recovery system is used as an activator, mixed with the heat-exchanged hot air (i.e., a mixture of steam and hot air), and returned to the upper section of the furnace via a return feeder; the remaining surplus steam is supplied externally. The heat-exchanged carbon activation tail gas enters the secondary cyclone separator.

[0111] In the above system, the oxygen generated by the air separator is divided into two paths: one path is introduced into the lower section of the furnace through the oxygen inlet at the bottom of the furnace for combustion support, and the other path is introduced into the activation zone of the upper section of the furnace through the return feeder to participate in the activation reaction. During startup, the fluidized bed carbon activation integrated furnace is preheated to the set temperature by the ignition burner; after normal operation, the volatiles released by the thermal decomposition of the raw materials are burned in the furnace, continuously providing heat for the reaction.

[0112] During system operation, the mixed raw materials are added through the feed inlet in the lower part of the furnace, where carbonization and activation reactions are completed. The resulting carbon-based powder adsorbent material is discharged from the top of the furnace along with the carbon activation tail gas. After the tail gas enters the primary cyclone separator, the larger particles separated are returned to the upper section of the furnace via a return feeder for further activation. The tail gas containing finer particles enters the waste heat recovery system for heat exchange, and then enters the secondary cyclone separator, where the larger particles are again returned to the upper section of the furnace via a return feeder. Finally, the tail gas containing finer particles enters the bag filter. After separation and filtration by the bag filter, the carbon activation tail gas enters the cooler for cooling. The condensate generated during the cooling process, along with desalinated and deoxygenated industrial water, enters the boiler water pump and is sent to the waste heat recovery system for heat exchange to generate steam. The fine powder collected by the bag filter through online pulse jet cleaning falls into the silo pump, and then, using nitrogen separated by the air separator as the carrier gas, it is sent to the collection and packaging via a pneumatic conveying system to obtain the carbon-based powder adsorbent material product.

[0113] Example 1

[0114] (1) Raw material ratio

[0115] Weigh out the following components by weight: 60 parts of semi-coke powder, 23 parts of carbonization and activation sieved granules from the activated carbon production process, 15 parts of sieved granules from flue gas purification using the activated carbon method, and 2 parts of fly ash. Mix thoroughly and set aside.

[0116] (2) Equipment preheating and atmosphere preparation

[0117] The fluidized bed carbon activation furnace is preheated to 550°C by adding fuel and turning on the ignition burner, while simultaneously activating the air separator to introduce oxygen into the bottom of the furnace to aid combustion. After the raw materials are fed into the furnace, the preheating stage ends, and the furnace enters the normal operation stage.

[0118] (3) Carbonization and activation

[0119] The mixture is fed into the fluidized bed carbonization and activation integrated furnace through the feed inlet in the middle and lower part. After the raw material enters the furnace, the larger particles settle to the carbonization zone in the lower section of the furnace due to gravity, where they are carbonized at the carbonization temperature and begin local activation; the smaller particles are carried by the rising hot air flow to the activation zone in the upper section of the furnace, where they are rapidly carbonized during the ascent and undergo deep activation at the activation temperature in the upper section.

[0120] The carbonization zone operates under a non-oxidizing atmosphere. Oxygen introduced from the furnace bottom combusts with the volatiles released from the pyrolysis of the raw materials near the bottom, consuming a large amount of oxygen; the carbonized material is effectively in a non-oxidizing atmosphere. The activation zone operates under an oxygen- and steam-containing atmosphere. The remaining gases (CO2, H2O, etc.) rising to the activation zone, along with a mixture of oxygen, steam, and hot air introduced through the return feeder, constitute the oxygen- and steam-containing activation atmosphere. In this atmosphere, oxygen accounts for 8% of the volume, and water vapor accounts for 60%.

[0121] The carbonization temperature in the lower section of the furnace is controlled at 700℃, and the carbonization time is 30 min; the activation temperature in the upper section of the furnace is controlled at 920℃, and the activation time is 30 min. The mixture of carbon activation tail gas and carbon-based powder adsorbent material generated by the reaction is discharged from the top of the furnace.

[0122] (4) Gas-solid separation and product collection

[0123] The mixture of carbon-activated tail gas and carbon-based powder adsorbent is separated into gas and solid phases by a primary cyclone separator. Larger carbon-based powder adsorbent particles are returned to the upper activation zone of the furnace for further activation via a return feeder, while tail gas containing finer particles is sent to the waste heat recovery system.

[0124] The waste heat recovery system adopts a partitioned heat exchanger, including a steam generator and a water heater, and produces low-pressure saturated steam as a byproduct. Part of the low-pressure steam is used as an activator in the fluidized bed carbon activation integrated furnace.

[0125] After heat exchange in the waste heat recovery system, the carbon-activated tail gas and carbon-based powder adsorbent material enter a secondary cyclone separator. The larger particles separated are returned to the upper activation zone of the furnace for further activation via a return feeder. The carbon-activated tail gas containing finer particles enters a bag filter. After separation and filtration, the carbon-activated tail gas is cooled by a cooler and can be reused. The fine powder collected by the online pulse jet cleaning of the bag filter falls into a silo pump, and then is sent to a silo for collection and packaging via a nitrogen pneumatic conveying system separated by an air separator, thus obtaining the finished carbon-based powder adsorbent material.

[0126] (5) Product performance testing

[0127] The iodine adsorption value of the finished carbon-based powder adsorbent material was determined according to GB / T 7702.7-2023, the methylene blue adsorption value was determined according to GB / T 7702.6-2008, and the specific surface area and pore volume were determined according to GB / T 7702.20-2025 (nitrogen adsorption method). Moisture, ash, and volatile matter were determined according to the GB / T 7702 series of standard methods. The fixed carbon content was calculated by the difference method (100% - moisture - ash - volatile matter).

[0128] Test results: Iodine adsorption value 902 mg / g, methylene blue adsorption value 195 mg / g, specific surface area 966 m² 2 / g, total pore volume 0.62cm³ 3 / g, moisture 0.7%, average ash 10.8%, volatile matter 2.8%, fixed carbon content 85.7%, and particle size below 325 mesh (44μm) accounts for 92%.

[0129] Example 2

[0130] Example 1 is repeated, except that the raw material ratio is as follows: 55 parts of semi-coke powder, 21 parts of carbonization and activation sieved particles from the activated carbon production process, 20 parts of sieved particles after flue gas purification by activated carbon method, and 4 parts of fly ash. Other conditions are the same as in Example 1.

[0131] Product test results: Iodine adsorption value 887 mg / g, methylene blue adsorption value 186 mg / g, specific surface area 952 m² 2 / g, moisture 0.6%, average ash 12.8%, volatile matter 2.8%, fixed carbon content 83.8%.

[0132] Example 3

[0133] This example is a single-factor study of activation temperature. Under the same raw material ratio and process conditions as in Example 1, the effects of different activation temperatures on the iodine adsorption value, methylene blue adsorption value, and specific surface area of ​​the product were investigated.

[0134]

[0135] Within the temperature range of 900–950℃, the adsorption performance increases with increasing temperature, but decreases above 950℃ due to over-activation leading to pore structure collapse. The above data also indicate that within the temperature range of 900–1000℃, the iodine adsorption value of the product meets the requirements for industrial applications (≥850 mg / g).

[0136] It should be noted that this embodiment focuses on the effect of activation temperature. When the carbonization temperature fluctuates within the range of 600~900℃, it mainly affects the degree of removal of volatiles, and has a relatively limited effect on the determination of the pore structure of the final product.

[0137] Example 4

[0138] This embodiment is a single-factor study of the ratio. Under the same process conditions as in Example 1 (carbonization temperature 700℃, activation temperature 920℃), the ratio of each raw material was changed to investigate its effect on the iodine adsorption value and methylene blue adsorption value of the product.

[0139] (1) Effect of the amount of semi-coke powder used

[0140] The following components were used: 23 parts of carbonization and activation sieved granules from the activated carbon production process, 15 parts of sieved granules from flue gas purified by activated carbon method, and 2 parts of fly ash. The amount of semi-coke powder was varied.

[0141]

[0142] The results showed that the adsorption performance was optimal when the amount of semi-coke powder was 50-70 parts.

[0143] (2) Impact of fly ash usage

[0144] The following ingredients were used: 60 parts of semi-coke powder, 23 parts of carbonization and activation sieved granules from the activated carbon production process, and 15 parts of sieved granules from flue gas purification using activated carbon. The amount of fly ash was varied.

[0145]

[0146] The results showed that the adsorption performance was significantly improved when the fly ash content was 1 to 5 parts, the catalytic effect was not obvious when the content was less than 1 part, and the performance decreased when the content was higher than 5 parts due to excessive ash content.

[0147] Based on the results of the single-factor experiments, the optimal ratio of the four raw materials is as follows: 50-70 parts of semi-coke powder, 15-30 parts of carbonization and activation sieved particles from the activated carbon production process, 10-20 parts of sieved particles after flue gas purification by activated carbon method, and 1-5 parts of fly ash.

[0148] It should be noted that during the formulation screening process, the single-factor analysis focused on semi-coke fragments and fly ash as the main variables. This is because these two, as the main carbon source and catalytic activation aid respectively, have the highest weighting in their impact on product performance. The carbon content, pore structure, and surface chemical properties of the carbonized activated granules from the activated carbon production process and the granules after flue gas purification using activated carbon are relatively stable. The optimal dosage of these components was determined based on a comprehensive assessment of the necessity verification results of proportions 2-3 (i.e., the negative impact on product performance when these components are absent). Ultimately, the optimal ratio range for the four raw materials was determined.

[0149] Comparative Example 1

[0150] The difference from Example 1 is that the raw material ratio is 60 parts of semi-coke powder, 23 parts of carbonization and activation sieved particles from the activated carbon production process, and 15 parts of sieved particles after flue gas purification by activated carbon method, without fly ash. Other conditions are the same as in Example 1.

[0151] Product test results: Iodine adsorption value 762 mg / g, methylene blue adsorption value 158 mg / g, specific surface area 848 m². 2 / g.

[0152] Compared to Example 1 (iodine adsorption value 902 mg / g, methylene blue adsorption value 195 mg / g), the iodine adsorption value decreased by 140 mg / g (a decrease of 15.52%) and the methylene blue adsorption value decreased by 37 mg / g (a decrease of 18.97%) after the absence of fly ash. This indicates that the catalytic effect of natural metal oxides in fly ash is crucial for improving the activation reaction efficiency, and the activation reaction efficiency is significantly reduced when fly ash is absent.

[0153] This comparative example demonstrates that in the absence of fly ash, the catalytic effect of natural metal oxides is lost, and the adsorption performance of the product decreases significantly.

[0154] Comparative Example 2

[0155] The difference from Example 1 is that the raw material ratio is 60 parts of semi-coke powder, 23 parts of carbonization and activation screening particles from the activated carbon production process, and 2 parts of fly ash, excluding screening particles from flue gas purification using the activated carbon method. Other conditions are the same as in Example 1.

[0156] Product test results: Iodine adsorption value 728 mg / g, methylene blue adsorption value 142 mg / g, specific surface area 802 m² 2 / g.

[0157] Compared to Example 1, the iodine adsorption value of the sieved particles after flue gas purification using activated carbon decreased by 174 mg / g (a decrease of 19.29%), and the methylene blue adsorption value decreased by 53 mg / g (a decrease of 27.18%). This indicates that the sieved particles after flue gas purification using activated carbon have formed a stable and abundant microporous-mesoporous network. Their existing mature pores can be directly integrated into the pore network of the finished product, becoming an important source of mesopores and macropores. When this component is missing, this part of the existing mesoporous-macroporous network is missing in the finished product, resulting in damage to the integrity of the pore structure and a significant reduction in total pore volume and adsorption performance.

[0158] This comparative example demonstrates that the incorporation of sieved particles after flue gas purification by activated carbon can directly contribute to the mesopores and macropores of the finished product, and the adsorption performance of the product decreases significantly when this component is lacking.

[0159] Comparative Example 3

[0160] The difference from Example 1 is that the raw material ratio is 60 parts of semi-coke powder, 15 parts of sieved granules after flue gas purification by activated carbon method, and 2 parts of fly ash, without the carbonization and activation sieved granules from the activated carbon production process. Other conditions are the same as in Example 1.

[0161] Product test results: Iodine adsorption value 745 mg / g, methylene blue adsorption value 148 mg / g, specific surface area 820 m². 2 / g.

[0162] Compared to Example 1, the iodine adsorption value decreased by 157 mg / g (a decrease of 17.41%) and the methylene blue adsorption value decreased by 47 mg / g (a decrease of 24.10%) after carbonization and activation sieving of the activated carbon production process. This indicates that the initial pore structure provided by the carbonization and activation sieving of the activated carbon production process plays an important guiding and promoting role in subsequent activation and pore formation; without this type of raw material, it is difficult to form a rich hierarchical pore structure during the activation process.

[0163] This comparative example demonstrates that when the carbonization, activation, and sieving of fragments are lacking in the activated carbon production process, the initial pore structure is missing, resulting in a significant decrease in the product's adsorption performance.

[0164] Comparative Example 4

[0165] The difference from Example 1 is that the raw material ratio is 23 parts carbonization and activation screening particles from the activated carbon production process, 15 parts screening particles after flue gas purification by activated carbon method, and 2 parts fly ash, excluding semi-coke fragments. Other conditions are the same as in Example 1.

[0166] Product test results: Iodine adsorption value 698mg / g, methylene blue adsorption value 125mg / g, specific surface area 758m² / g.

[0167] Compared to Example 1, the iodine adsorption value decreased by 204 mg / g (a decrease of 22.62%) and the methylene blue adsorption value decreased by 70 mg / g (a decrease of 35.90%) after the absence of semi-coke fragments. This indicates that the high fixed carbon skeleton provided by semi-coke fragments is the material basis for the development of the product's pore structure; without semi-coke fragments, the fixed carbon content of the system is insufficient, making it difficult to form a well-developed pore structure.

[0168] This comparative example demonstrates that when semi-coke fragments are lacking, the high fixed carbon framework is missing, and the adsorption performance of the product decreases significantly.

[0169] Comparative Example 5

[0170] The difference from Example 1 is that 60 parts of semi-coke powder were used, and the other three raw materials were not included. All other conditions were the same as in Example 1.

[0171] Product test results: Iodine adsorption value 655 mg / g, methylene blue adsorption value 112 mg / g, specific surface area 665 m² 2 / g.

[0172] The adsorption performance of Comparative Example 5 was significantly lower than that of Example 1, indicating that single semi-coke fragments are difficult to form a rich micropore-mesopore network under conventional physical activation conditions. This is because although semi-coke fragments have a macroporous structure formed by volatilization, there are insufficient effective micropore and mesopore adsorption sites, and their carbonaceous structure has a greater tendency to graphitize, thus limiting pore development when activated alone.

[0173] This comparative example demonstrates that a single raw material cannot produce a good adsorbent material product, further illustrating the necessity of the synergistic effect of the four raw materials.

[0174] The performance test results of the products obtained from each embodiment and comparative example are summarized in Table 1.

[0175] Table 1. Process parameters and performance test results of each embodiment and comparative example.

[0176]

[0177] Results analysis:

[0178] First, the iodine adsorption values ​​of Examples 1-3 (with all four raw materials) in Table 1 are between 887 and 919 mg / g, and the methylene blue adsorption values ​​are between 186 and 203 mg / g, which are significantly better than all comparative examples.

[0179] Second, the iodine adsorption values ​​of Comparative Examples 1-4 (each lacking one of the four raw materials) were only 698-762 mg / g, and the methylene blue adsorption values ​​were only 125-158 mg / g, both significantly lower than the examples with all four raw materials present. The lack of any one of the four raw materials resulted in a significant decrease in the adsorption performance of the product, indicating that each of the four raw materials is indispensable and plays an irreplaceable synergistic role.

[0180] Third, the iodine adsorption value of Comparative Example 5 (single semi-coke fragments) was only 655 mg / g, further illustrating that it is difficult to obtain good activated carbon products from a single waste.

[0181] The above results fully demonstrate the synergistic effect among the four specific carbon-based or coal-based wastes of this invention—the adsorption performance of the combination of the four raw materials is much greater than the sum of the performance of each single raw material or the absence of any one raw material, and all four raw materials are indispensable.

Claims

1. A method for preparing a carbon-based powder adsorbent material, the method comprising the following steps: S1. Mix semi-coke powder, carbonization and activation sieved granules from the activated carbon production process, sieved granules after flue gas purification by activated carbon method, and fly ash to obtain a mixture. S2. The mixture is fed into the reactor for carbonization and activation reaction. The carbon-based powder adsorbent material generated during the reaction is discharged from the reactor with the tail gas flow. S3. Perform gas-solid separation on the mixture of exhaust gas and the carbon-based powder adsorbent material, and collect the fine powder to obtain the finished carbon-based powder adsorbent material.

2. The preparation method according to claim 1, characterized in that: In step S1, the mixture comprises, by weight, 50-70 parts of semi-coke powder, 15-30 parts of carbonization and activation screening particles from the activated carbon production process, 10-20 parts of screening particles after flue gas purification by activated carbon method, and 1-5 parts of fly ash.

3. The preparation method according to claim 1 or 2, characterized in that: In step S2, the reactor is a fluidized bed carbon activation integrated furnace; the furnace chamber of the fluidized bed carbon activation integrated furnace is divided into a lower carbonization zone and an upper activation zone.

4. The preparation method according to claim 3, characterized in that: The activation zone is activated in an oxygen- and steam-containing atmosphere; preferably, the oxygen generated by air separation is divided into two paths: one path is introduced into the activation zone of the fluidized bed carbon activation integrated furnace to participate in the activation reaction, and the other path is introduced into the bottom of the fluidized bed carbon activation integrated furnace for combustion support.

5. The preparation method according to any one of claims 1-4, characterized in that: In step S1, the raw materials are crushed and screened before mixing to obtain granules with a particle size ≤ 5 mm, preferably granules with a particle size ≤ 4 mm.

6. The preparation method according to any one of claims 1-5, characterized in that: The process includes a preheating step of the reactor before step S2; preferably, the reactor is preheated to 300~650°C, more preferably 400~600°C.

7. The preparation method according to any one of claims 1-6, characterized in that: In step S2, the carbonization reaction temperature is controlled at 600~900℃, preferably 620~850℃, more preferably 650~800℃; and / or In step S2, the activation reaction temperature is controlled at 900~1000℃, preferably 900~950℃.

8. The preparation method according to any one of claims 1-7, characterized in that: The gas-solid separation in step S3 includes: subjecting the mixture of exhaust gas and carbon-based powder adsorbent material to primary cyclone separation, secondary cyclone separation and dust removal treatment in sequence; preferably, the larger carbon-based powder adsorbent material particles separated by primary cyclone separation and / or secondary cyclone separation are returned to the reactor to continue participating in the activation reaction. Preferably, the proportion of particles with a particle size ≤44μm in the finished carbon-based powder adsorbent material is ≥90%, preferably ≥92%.

9. The preparation method according to claim 8, characterized in that: A waste heat recovery step is provided between the primary cyclone separation and the secondary cyclone separation. After the mixture of exhaust gas and carbon-based powder adsorbent material is separated by the primary cyclone separation, the carbon-activated exhaust gas containing finer carbon-based powder adsorbent material is first subjected to waste heat recovery, and then subjected to secondary cyclone separation and dust removal treatment in sequence. The fine powder collected is the finished carbon-based powder adsorbent material. Preferably, part of the steam generated in the waste heat recovery step is returned to the reactor as an activator to participate in the activation reaction.

10. A carbon-based powder adsorbent material, characterized in that: The carbon-based powder adsorbent material is prepared by the method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Preparing method for coal-based active carbon for controlling environmental protection and control

    CN106517188A

  • System and method for preparing activated carbon by integrating coal / biomass carbonization and activation

    CN112029518A

  • Coal-based powdered activated carbon with high strength and high specific surface area and preparation method of coal-based powdered activated carbon

    CN119038545A